Efficacy and safety of Janus kinase inhibitors in non-infectious inflammatory ocular diseases: a prospective cohort study from the international AIDA network registries - Vitale, Antonio; Palacios-Olid, Judith; Caggiano, Valeria; Ragab, Gaafar; Hernández-Rodríguez, José; Pelegrín, Laura; Mejía-Salgado, Germán; Zarate-Pinzón, Laura; Gentileschi, Stefano; Sota, Jurgen; Fonollosa, Alex; Carreño, Ester; et al. (Frontiers in Medicine, 2024)
Introduction: Non-infectious inflammatory ocular diseases pose significant challenges in diagnosis and management, often requiring systemic immunosuppressive therapy. Since Janus kinase (JAK) inhibitors may represent a novel therapeutic option for these disorders, the present study aimed to expand current knowledge about their efficacy and safety in patients with these conditions. Methods: This prospective cohort study included 12 adult patients from the international Autoinflammatory Disease Alliance (AIDA) Network registries dedicated to non-infectious ocular inflammatory conditions. We assessed ocular flares, visual acuity, disease course, and complications before and after initiating JAK inhibitor therapy. Results: Ocular inflammation was related to a systemic disease in 8 (66.7%) patients as follows: spondyloarthritis (n=3), peripheral psoriatic arthritis (n=1), rheumatoid arthritis (n=1), antinuclear antibodies (ANA) positive juvenile idiopathic arthritis (n=1), Behçet’s syndrome (n=1), Vogt-Koyanagi-Harada syndrome (n=1). In total, 4 patients received baricitinib, 1 patient received tofacitinib, and 7 patients underwent upadacitinib treatment. The overall average duration of JAK inhibitors treatment was 8.6±5.5 months (ranging from 3 to 20 months). At the last assessment, ocular disease control was complete in 12/12 patients. One patient discontinued baricitinib due to poor compliance after a 12-month relapse-free period. The incidence of ocular flares was 125 episodes/1.000 person-months prior to the initiation of JAK inhibitors and 28.6 episodes/1.000 person-months thereafter. The incidence rate ratio for experiencing a relapse before starting a JAK inhibitor compared to the following period was 4.37 (95% C.I. 1.3-14.7, p-value: 0.02). Conclusion: JAK inhibitors demonstrate efficacy and safety in controlling ocular inflammatory relapses, confirming that they represent a valuable treatment option for patients with non-infectious inflammatory ocular diseases resistant to conventional treatments.